2022
DOI: 10.1038/s41598-022-25602-7
|View full text |Cite
|
Sign up to set email alerts
|

Short course palliative radiotherapy in advanced solid tumors: a pooled analysis (the SHARON project)

Abstract: Previous trials showed the tolerability and efficacy of a palliative radiotherapy (RT) regimen (SHARON) based on the 4 fractions delivered in 2 days in different oncological settings. In order to identify possible predictors of symptomatic response, the purpose of this study is to perform a pooled analysis of previous trials. We analyzed the impact on symptomatic response of the following parameters: tumor site, histological type, performance status (ECOG), dominant symptom, and RT dose using the Chi-square te… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 21 publications
0
3
0
Order By: Relevance
“…However, many studies have demonstrated that initiating palliative treatment at earlier stages of the disease leads to less aggressive care, more adequate pain management, an improved quality of life, and increased survival rates [ 13 , 21 , 22 , 23 ]. Moreover, referring patients to palliative RT earlier may increase the probability of achieving a better pain response and overall treatment outcomes [ 24 ].…”
Section: Discussionmentioning
confidence: 99%
“…However, many studies have demonstrated that initiating palliative treatment at earlier stages of the disease leads to less aggressive care, more adequate pain management, an improved quality of life, and increased survival rates [ 13 , 21 , 22 , 23 ]. Moreover, referring patients to palliative RT earlier may increase the probability of achieving a better pain response and overall treatment outcomes [ 24 ].…”
Section: Discussionmentioning
confidence: 99%
“…In this case, the patients are most frequently metastatic and the objective of the treatment is to treat a symptom. The doses are often much lower, typically 30 Gy in 10 fractions or 20 Gy in 5 fractions [31]. Examples are irradiation of bone metastases for analgesic purposes [32], whole brain irradiation when patients have brain metastases and a risk of intracranial hypertension [33,34], mediastinal irradiation when patients have compressive mediastinal tumors [35], and irradiation for hemostatic purposes when patients have very hemorrhagic tumors [36].…”
Section: Irradiation With Palliative Intentmentioning
confidence: 99%
“…Among factors to consider are an intervention’s aim, e.g., life-prolonging versus symptom-directed, and time-frame aspects such as remaining life time and duration of treatment. Palliative radiotherapy is among the most effective and cost-effective interventions and can be tailored to individual patients’ need and preferences [ 2 5 ]. Extreme hypofractionation cuts treatment duration into a fraction of what is needed to complete traditional regimens, e.g.…”
Section: Introductionmentioning
confidence: 99%